Master Class - New trends in accounting: Integrated Reporting [INV] - Lopes, A.I. (Master Class, Universidade Europeia, 2020)
Master Class to the students of "Master International Management", in the unit "Management Seminars". The topic covers the "Integrated Reporting" stream as a new trend in Accounting.